Zinc-responsive acral hyperkeratosis: A report of a rare entity - Priyanka A Kowe; Ravi Bhushan; Vaishali H Wankhade; Rajesh P Singh (Wolters Kluwer Medknow Publications, 2021)
Chronic acral hyperkeratotic dermatosis includes several conditions such as lichen simplex chronicus (LSC), hypertrophic lichen planus (HLP), psoriasis vulgaris (Ps), acral acanthosis nigricans, acquired zinc deficiency, and necrolytic acral erythema (NAE). LSC, Ps, and HLP respond to conventional treatments such as topical corticosteroids, immuno-modulators such as tacrolimus, and oral methotrexate. Zinc-responsive acral hyperkeratosis is a novel entity that resembles the above mentioned diagnoses clinically but fails to respond to the above treatment options. NAE is a rare condition, commonly associated with hepatitis C virus infection and manifest similar clinical features of zinc-responsive acral hyperkeratosis, but differs histopathologically. Both conditions show a good response to oral zinc supplementation. As there is a paucity of literature on zinc-responsive acral hyperkeratosis, we are highlighting the case.